Συστήματα εἰσροῆς ἀνθρώπινου δυναμικοῦ στὶς οἰκογένειες τῆς Λευκάδας τοῦ 18ου αἰώνα - ΑΡΓΥΡΟΥ, ΕΦΗ (Μνήμων, 2011)
A comparative approach of the contracts concerning the employment of childrenby Lefkada families during the 18th century is dealt with in the presentarticle. The comparison is carried out with a double criterion: on the one handthe employment with or without a salary and on the other hand the sex. Asfar as the first criterion is concerned we observe that despite the corrodingfunction of the market, the society in question perpetuates the traditionalmethods of reinforcement of families with male and female dynamic. Thecontracts concerning children that are employed with a salary (κοπέλι-δου-λευτής and κοπέλα-δουλεύτρα) are the minority. Families usually adopt aparticular relationship that ranges between the family relationship and theworking one (ψυχοπαίδι and ψυχοπαίδα). In the latter, it is obvious in thecontracts concerning a girl, either in verbal level or in the level of terms thatthe working character prevails the family one. Either with a salary relationshipor without one a girl is considered domestic help, that is the reason why sheis employed mainly by the upper class in town. On the contrary when dealingwith contracts concerning boys in the verbal level, it is clear that a family typerelationship is dominant. Through this relationship both the foster family andthe child’s needs will be met and it is for this reason that boys are employedby the middle classes both in town and in the villages. Nevertheless, accordingto certain terms the employed boy is demoted in certain cases to the positionof a labourer.From the comparison of the relevant contracts it is shown that the positionof the employed girl is worse than that of a boy. This applies to the relationshipshe has with the foster family which in turn controls her tightly and alsoto her final salary. Although the whatever newer elements in the workingrelationships are noticed in the contracts with salaries of boys, the boys thatenter the families with a no-salary contract are in a better position than thatof the boys with a salary one.